2016
DOI: 10.1002/2016ja022538
|View full text |Cite
|
Sign up to set email alerts
|

The response of the temperature of cold‐point mesopause to solar activity based on SABER data set

Abstract: The thermal structure and energy balance of upper atmosphere are dominated by solar activity. The response of cold‐point mesopause (CPM) to solar activity is an important form. This article presents the response of the temperature of CPM (T‐CPM) to solar activity using 14 year Sounding of the Atmosphere using Broadband Emission Radiometry data series over 80°S–80°N regions. These regions are divided into 16 latitude zones with 10° interval, and the spatial areas of 80°S–80°N, 180°W–180°E are divided into 96 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…is smaller than the seasonal and daily variations. The OH equivalent temperature solar response is in agreement with that derived by Tang et al (2016) and Kalicinsky et al (2016) (4.89 K per 100 s.f.u. and 4.2 K per 100 s.f.u., respectively) but larger than that of Kim et al (2017) (1.2 K per 100 s.f.u.…”
Section: Sabersupporting
confidence: 89%
“…is smaller than the seasonal and daily variations. The OH equivalent temperature solar response is in agreement with that derived by Tang et al (2016) and Kalicinsky et al (2016) (4.89 K per 100 s.f.u. and 4.2 K per 100 s.f.u., respectively) but larger than that of Kim et al (2017) (1.2 K per 100 s.f.u.…”
Section: Sabersupporting
confidence: 89%
“…The differences are apparently due to the different altitudes, since the correlation between ozone and temperature increases with increasing altitude in the middle to upper atmosphere (~70 to ~100 km; Huang et al, , ). The ozone density data we analyzed in this paper are located at the mesopause, which has a global average altitude of 95.4 ± 0.5 km (Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from Figures a and b, the 95‐km altitude layer is not only the kinetic temperature minimum region in the middle atmosphere but also the maximum region of ozone VMR in the altitude range from ~25 to ~105 km, circled in blue in Figures a and b. Because the global average altitude of mesopause is around 95.4 ± 0.5 km (Tang et al, ), the blue circle symbols shown in Figures a and b are just around the mesopause region, in which the radiative, chemical, and dynamical processes are vigorous (Beig et al, , ). We have investigated the response of T‐CPM to solar activity in previous paper.…”
Section: Methods Of Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In their review, Beig et al (2008) list numerous studies showing that the response of the mesospherelow thermosphere temperature to the change in solar activity reaches 4-5 K / 100 SFU, where SFU is the solar radio flux at a wavelength of 10.7 cm in 10 −22 W M −2 Hz −1 (F10.7). Tang et al (2016) estimated the change in the temperature of the mesopause from 2002 to 2015 using the measurements of the SABER radiometer on board the TIMED satellite. They showed that the average global response is about 5 K/100 SFU, in agreement with the results given in the review of Beig et al (2008).…”
Section: Introductionmentioning
confidence: 99%